Swing along! - Cook, Will Marion; State Theatre (Sydney, N.S.W.); Baron, Maurice, 1889-1964 (1900)
Part of the State Theatre collection of cinema scores and parts, mainly used for silent movies, but including musical materials associated with talking pictures ca. 1900-1950, used by the State Theatre and various film distribution companies throughout Australia. Some items include performance annotations.
Stamped: Film House Library.
The stamped marking on the material indicates the film distribution companies or theatres that owned, used, or distributed the music to other cinemas.
Keywords: Dramatic music; Instrumental music -- Scores and parts; Silent film music